The Navier–Stokes equations with the Neumann boundary condition in an infinite cylinder - Abe, K. (Manuscripta mathematica, 2019)
We prove unique existence of local-in-time smooth solutions of the Navier–Stokes equations for initial data in L p and p ∈ [ 3 , ∞ ) in an infinite cylinder, subject to the Neumann boundary condition.